Assessing Balance Recovery in Post-ACL Reconstruction Patients Using the Mini-Balance Evaluation Systems Test (Mini-BESTest) - Bustam, Ika Guslanda (FISIO MU: Physiotherapy Evidences, 2025)
Introduction: Injuries to the anterior cruciate ligament (ACL) are some of the most prevalent musculoskeletal injuries, especially among athletes and those participating in high-impact sports or physical activities. To evaluate balance recovery in patients following Anterior Cruciate Ligament (ACL) reconstruction using the Mini-Balance Evaluation Systems Test (Mini-BESTest). Methods: This study assessed the balance abilities of post-ACL reconstruction patients by administering the Mini-BESTest. A total of 50 patients participated, completing the test at 6 months post-surgery. The results were compared to a control group of healthy individuals to determine the effectiveness of the Mini-BESTest in identifying balance deficits post-reconstruction. Results: The Mini-BESTest scores indicated significant differences in balance abilities between the post-ACL reconstruction group and the healthy control group (p<0.03). Patients demonstrated improved balance over time, but still showed deficits compared to healthy peers. Factors such as age, gender, and time since surgery were analysed for their impact on balance recovery. Conclusion: The Mini-BESTest proved to be a valuable tool for assessing balance recovery in post-ACL reconstruction patients. While improvements were noted, there remains a need for targeted rehabilitation to fully restore balance. This study highlights the utility of the Mini-BESTest in clinical settings to monitor and guide rehabilitation strategies.